Математическое симулирование энергетических и экономических параметров двигателя 4DC-125/110 работающего на различных видах топлива на основании теплового расчета - Дикий, А. А.; Воляк, П. С.; Банарь, Э. П.; Дикий, О. А.; Банарь, Е. П.; Dichii, А.; Voleac, P.; Banari, E. (ЦНТУ, 2019)
В статье представлена математическая модель теплового расчета двигателей с воспламенением от сжатия. В качестве примера выбрана конкретная модель 4DC-125/110, на основе которой определены энергетические и экономические показатели двигателя для питания альтернативными видами топлива с целью выявления наилучших результатов. Использование результатов теоретического анализа на практике позволит более эффективно и обоснованно подходить к выбору топлива для дизельных двигателей внутреннего сгорания. У статті наведено математичну модель теплового розрахунку двигунів із запалюванням від стиснення. Як приклад обрано конкретну модель 4DC-125/110 на основі якої визначені енергетичні та економічні показники двигуна для живлення альтернативними видами палива з метою виявлення найкращих результатів. Використання результатів теоретичного аналізу на практиці дозволить більш ефективно і обґрунтовано підходити до вибору палива для дизельних двигунів внутрішнього згоряння. The aim of this work is to perform thermal calculation for the engine model 4DC-125/110. Thermal calculation of an engine that runs on various types of fuel allows the assessment of economic and energy parameters. Using the results of theoretical analysis in practice will allow a more efficient and justified approach to the choice of fuel. To obtain a mathematical model of the thermal calculation of a diesel engine, the initial parameters were adopted: engine speed, number of cylinders, compression ratio, engine displacement, pressure and ambient temperature, pre-heating of the mixture, manifold pressure, exhaust gas temperature, pressure increase degree, excess air coefficient, heat utilization coefficient, indicator completeness coefficient and fuel energy power . At the same time, the following were considered as fuel: clean diesel, mixtures of diesel with methane, diesel with biofuel, and also a mix of methane and biofuel. The proportions of the components were, respectively, 80% to 20%. The dependences of the influence of the quantitative and qualitative composition of the fuel on the indicator and effective efficiency, specific fuel efficiency, torque and engine power are obtained. The graphical dependence of the influence of the quantitative and qualitative composition of the fuel on the effective engine power is shown, from which it follows that the lowest indicator has an engine that runs on a mixture of biofuel and methane, as well as diesel and biofuel. Based on the mathematical model of thermodynamic calculation for the selected engine and simulation of its characteristics for it supplying by various fuel mixtures with traditional is obtained that the effective power is reduced with 16,6% (49 kW) from the factory’s power if 20% of the mass of diesel fuel are substitution by methane; accordingly, in the case of substitution of 20% traditional fuel by biofuel is observed a power’s decrease with 2,38% (57,4 kW) and for the last case is obtained a 25% (43,9 kW) decrease if fuel mixture are made by 80% of biofuel and 20% of methane. Drawing a parallel between the effective power and economic characteristics of the engine, which are reflected in the specific fuel consumption and efficiency, it is clearly seen that the most economical case is obtained when the engine is supplying with a combustible mixture of diesel fuel and methane, when it work on the so-called thermodynamic gas-diesel cycle.
Математичне симулювання енергетичних та економічних параметрів двигуна 4DC-125/110, який працює на різних видах палива на підставі теплового розрахунку
Mathematical Simulation of Energetics and Economics Parameters of the 4DC-125/110 Engine Based on Thermodynamical Calculation Supplying by Various Types of Fuel
Keywords: биотопливо; метан; дизтопливо; тепловой расчет; традиционное топливо; рапсовое масло; эффективная мощность; термодинамический газодизельный цикл; біопаливо; метан; дизпаливо; тепловий розрахунок; традиційне паливо; рапсове масло; ефективна потужність; термодинамічний газодизельний цикл; mathematical model; combustibles; diesel fuel; methane; biofuel; effective power; excess air coefficient; exhaust gases; gas emission; autovehicule’s engines